アイスコアとフィルン空気の分析から探る氷期の南極内陸におけるフィルンの厚さ - 川村, 賢二; Kawamura, Kenji (2016)
アイスコアに含まれる空気は、もともとはフィルン（氷床上部の通気性のある層、５０～１００ｍ程度）の底部で大気から隔絶されたものであるため、同じ深度の氷より常に若くなる。この「氷と空気の年代差」は涵養量とフィルンの厚さに応じて空間的・時間的に変化する。低涵養量の南極内陸では、現在で2500年、氷期の最寒期では5000年ほどに達するため、その正確な推定は古環境復元にとって重要である（特に、二酸化炭素濃度と南極の気温の変動の時間関係を知りたい場合など）。氷と空気の年代差の推定にはフィルンの圧密モデルを用いるが、モデルが推定する氷期のフィルンの厚さと、アイスコアの気体（窒素やアルゴン）の重力分離から推定される厚さとの間に３０－４０ｍもの大きな隔たりがあり、長年の問題となっている。この問題は、氷期のフィルンの表層付近で深い対流混合が発達して気体の重力分離を妨げていたなら説明可能である。この可能性を検証するために、フィルン空気やアイスコアの重い希ガス（クリプトン、キセノン）の同位体比をもとに対流混合の度合いを推定した。その結果、南極内陸のドームふじとボストークでは、氷期の対流混合層は発達していなかったことが推察された。アイスコアのデータは、これらの地点のフィルンが氷期に薄くなったことを示唆し、既存の圧密モデルでは含まれていない大きな効果が存在するか（不純物の影響など）、温度と涵養量の効果が定量的に正しく表現されていない可能性を示した。 Ice cores provide records of past climate, atmospheric composition and glaciological conditions. In order to establish the age difference between ice and gas (e.g. Antarctic temperature and CO2), firn densification models are generally employed for estimating the past firn thickness. However, N2 and Ar isotopes from the Antarctic interior (e.g. Vostok, Dome Fuji, Dome C) for glacial periods have shown significantly smaller gravitational fractionation (equivalent to 30-40 m of firn thickness) than predicted by models. This discrepancy may be explained if a deep air convection, which eliminates isotopic fractionation at the top part of firn, was extremely well developed during glacial periods. We show, however, by measuring isotopic ratios of Kr, Ar and N2 from the Dome Fuji ice core, that a deep convective zone was not developed during the last glacial maximum (LGM). Because Kr has smaller diffusivity than Ar and N2, it is less gravitationally fractionated in deep firn if strong convective mixing exists. We developed a method to measure these gases in ice-cores, and applied it to the Dome Fuji core over the last ~30,000 years. When normalized to unit mass difference and corrected for thermal signal, the differences between N2 and Kr isotopic ratios are similar for the Holocene and LGM, suggesting similar size of convection zone in those periods. The Vostok core showed the same results for the ...